Auditoría Financiera al Gobierno Autónomo Descentralizado Parroquial de Sabanilla, Cantón Zamora, Período 2022. - Gueledel Abrigo, Jessica Maribel (2024)
The present work called FINANCIAL AUDIT TO THE PARISH DECENTRALIZED AUTONOMOUS GOVERNMENT OF SABANILLA, ZAMORA CANTON, PERIOD 2022, was developed through bibliographic consultation of the theoretical references that contrasts the theoretical part with the practice, to obtain information, an interview was conducted which was oriented to meet the objectives, which were: To evaluate the internal control of the Autonomous Decentralized Parish Government of Sabanilla Zamora canton to determine its compliance, for this purpose, a visit was made and a questionnaire was applied to the President and the Secretary- Treasurer of the Parish Government, to obtain information on the accounting process and control. The second objective refers to determining the reasonableness of the balances of the components that make up the statement of financial position and the legality of all transactions carried out in the Autonomous Decentralized Parish Government of Sabanilla, period 2022, to comply with this objective, documents that support the transactions were obtained to examine them and determine if the operations are carried out under the regulations that govern it. Finally, the financial audit report was prepared to comply with the third objective, it details the results obtained in the process, in this report are detailed the findings found with their respective conclusions and recommendations that serve for the entity to improve internal control of its administrative and financial activities. By conducting the financial audit in the Autonomous Decentralized Parish Government of Sabanilla, period 2022, it was concluded that it has adequate internal control management, its financial statements maintain reasonableness with their balances, except for the account of non-current assets, where it was evidenced that the long-lived assets that are damaged or in poor condition and have not been discharged.